Short-term Tuna fishing community: the dwellings in the 30s and 60s - Batista, Nuno (2019)
IOP Conference Series: Materials Science and Engineering PAPER • THE FOLLOWING ARTICLE ISOPEN ACCESS Short-Term Tuna Fishing Community: The Dwellings in the 30s and 60s Nuno Batista1 and Marta Marcal Goncalves1 Published under licence by IOP Publishing Ltd IOP Conference Series: Materials Science and Engineering, Volume 603, Issue 2 Citation Nuno Batista and Marta Marcal Goncalves 2019 IOP Conf. Ser.: Mater. Sci. Eng. 603 022091 DownloadArticle PDF References 58 Total downloads Turn on MathJax Share this article Share this content via email Share on Facebook (opens new window) Share on Twitter (opens new window) Share on Mendeley (opens new window) Article information Abstract This article describes the dwellings of a short-term tuna fishing community settled in Faro beach, Algarve, Portugal, between the 30s and 60s, that already disappeared. It is related how the change from the reed houses to the wooden sheds took place and how was the day-by-day of fishermen and their families during the tuna fishing season, from March to June. In the course of this research it was discovered that such fishing community took place in Faro beach for long decades, involved a large group of fishermen and their families that lived there, in a structured way. The main results we hope to achieve are the general awareness of this heritage and its dissemination. This research was based on documentary analysis, photographic and bibliographic research but, more importantly, interviews with people involved in this art, that still remains. During the development of this research, limitations were found due to the scarcity of available information and to the advanced age of the people involved, now with around 90 years old. That's why there's an urgency to make an adequate registration and disclosure of this heritage. This paper is original because there aren't many works about this theme under this point of view, taking Faro beach as object of study. As a vernacular heritage, it must be valued, so, publishing such work would influence the society in general, but primarily, the region's society, to alert them to a value that has been forgotten and, at the same time, clarify the future generations, helping to preserve the collective memory of a professional art that disappeared from the Algarve.